Dampak Pemekaran Wilayah Terhadap Pembangunan Bidang Sosial Dan Infrastruktur Wilayah - Baban Sobandi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2005)
This article explain about the result of the research on impact of the expansion of region, a case study in Kabupaten Tasikmalaya. The impacts studied are the ones over the development of social life and regions infrastuctures. This study finds out that the expansion of region maintains and even broadens the developments gaps between urban and rural areas. The gaps occur in many sectors such as income, education, health, and public facilities. This study suggests that a feasibility study must be done prior to expansion of region so that no significant gaps occur between the old and new regional.